A modelling approach and module for salinity management in drip irrigation. (July 2021) - Friedman, Shmulik P.; Gamliel, Alon
Abstract : The article describes a new modelling approach and module for soil salinity management. The two major objectives of the module are to simulate the seasonal course of the salinity of the soil solution in the active root zone of drip-irrigated crops to assist irrigators to optimise irrigation and salt leaching, and to help evaluate the salt fluxes in the deep percolating water for assessing the longer-term salt load of the irrigated crops on the regional ground and surface water resources. The module is based on the solutions of the DIDAS program for quasi-steady water flow and uptake for various drip irrigation scenarios, and on differentiating the applied water to evaporation from the soil surface, uptake by the plant roots, deep percolation through the root zone that leaches salt out of it, and deep percolation outside of the root zone that does not leach salts. After laying out the rationale behind the suggested approach and outlining the expressions used in the module for evaluating the salinity of the root zone, several sample computations, in silico experiments, are performed to illustrate the module functionality and its potential application, and to serve for sensitivity analysis of the system parameters. Additional investigation is needed into the adequacy of the suggested modelling approach and the developed module to simulate soil salinity in the active root zone. Highlights: The module evaluates seasonal courses of root zone salinity in drip-irrigated fields. It simulates root system development but does not predict plant growth and yields. It is based on modelling quasi-steady water flow and uptake and salt mass balance. The deep percolating water are partitioned into two fractions. One that flows through the root zone and leaches salt out of it, and one that flows around it.